Maternal exposure to polychlorinated biphenyls and the secondary sex ratio: an occupational cohort study - Waters Martha A; Lawson Christina C; Ruder Avima M; Deddens James A; Bertke Stephen J; Rocheleau Carissa M; Hopf Nancy B; Riggs Margaret A; Whelan Elizabeth A (BMC, 2011)
Abstract Background Though commercial production of polychlorinated biphenyls was banned in the United States in 1977, exposure continues due to their environmental persistence. Several studies have examined the association between environmental polychlorinated biphenyl exposure and modulations of the secondary sex ratio, with conflicting results. Objective Our objective was to evaluate the association between maternal preconceptional occupational polychlorinated biphenyl exposure and the secondary sex ratio. Methods We examined primipara singleton births of 2595 women, who worked in three capacitor plants at least one year during the period polychlorinated biphenyls were used. Cumulative estimated maternal occupational polychlorinated biphenyl exposure at the time of the infant's conception was calculated from plant-specific job-exposure matrices. A logistic regression analysis was used to evaluate the association between maternal polychlorinated biphenyl exposure and male sex at birth (yes/no). Results Maternal body mass index at age 20, smoking status, and race did not vary between those occupationally exposed and those unexposed before the child's conception. Polychlorinated biphenyl-exposed mothers were, however, more likely to have used oral contraceptives and to have been older at the birth of their first child than non-occupationally exposed women. Among 1506 infants liveborn to polychlorinated biphenyl-exposed primiparous women, 49.8% were male; compared to 49.9% among those not exposed (n = 1089). Multivariate analyses controlling for mother's age and year of birth found no significant association between the odds of a male birth and mother's cumulative estimated polychlorinated biphenyl exposure to time of conception. Conclusions Based on these data, we find no evidence of altered sex ratio among children born to primiparous polychlorinated biphenyl-exposed female workers.